Antenatal Corticosteroids for Preterm Premature Rupture of Membranes: Single or Repeat Course? - Brookfield, Kathleen F.; El-Sayed, Yasser Y.; Chao, Lisa; Berger, Victoria; Naqvi, Mariam; Butwick, Alexander J. (American Journal of Perinatology, 2015)
Objective The aim of this article is to determine the risk of maternal chorioamnionitis and neonatal morbidity in women with preterm premature rupture of membranes (PPROM) exposed to one corticosteroid course versus a single repeat corticosteroid steroid course.Study Design Secondary analysis of a cohort of women with singleton pregnancies and PPROM. The primary outcome was a clinical diagnosis of maternal chorioamnionitis. Using multivariate logistic regression, we controlled for maternal age, race, body mass index, diabetes, gestational age at membrane rupture, preterm labor, and antibiotic administration. Neonatal morbidities were compared between groups controlling for gestational age at delivery.Results Of 1,652 women with PPROM, 1,507 women received one corticosteroid course and 145 women received a repeat corticosteroid course. The incidence of chorioamnionitis was similar between groups (single course = 12.3% vs. repeat course = 11.0%; p = 0.8). Women receiving a repeat corticosteroid course were not at increased risk of chorioamnionitis (adjusted odds ratio, 1.28; 95% confidence interval, 0.69–2.14). A repeat course of steroids was not associated with an increased risk of any neonatal morbidity.Conclusion Compared with a single steroid course, our findings suggest that the risk of maternal chorioamnionitis or neonatal morbidity may not be increased for women with PPROM receiving a repeat corticosteroid course.
Keywords: steroids; chorioamnionitis; fetal membranes; premature rupture